Analysis Of Student Satisfaction Level With Academic Administration Services Agribusiness Study Program Department Of Agricultural Social Economics Faculty Of Agriculture Bengkulu University - Ilmayati, Ilmayati; Koldi Sudiansyah; Irvan Diyahya (International journal of technology and education research, 2023)
Satisfaction with academic services is important and needs to be considered in order to achieve quality service standards in improving performance. Every semester, students will be in contact with academic and administrative departments regarding lectures, seminars, exams, practicums and others. This research aims to determine the level of satisfaction of agribusiness students with the academic administration services of the Bengkulu University agribusiness study program. Respondents in this study were agribusiness study program students in the classes of 2017, 2018, 2019, 2020, and 2021. Analysis of student satisfaction with administrative services was measured through student perceptions (perceived service) of 5 indicators of academic service quality which include tangibles, reliability ( reliability), responsiveness, assurance and empathy. Next, validity and reliability tests were carried out using the SPSS 22 program. Measurement of satisfaction indicators was analyzed using a Likert scale and analysis using the CSI (customer satisfaction index) method. The research results show that the data validity test for each variable can be said to be valid. Meanwhile, the data reliability test has a Cronbach's Alpha value of 0.980, which means that the data has very strong reliability. The tangible dimension has the highest score which indicates the level of student satisfaction in the very satisfied category. Meanwhile, the dimensions of reliability, responsiveness, assurance and empathy indicate the level of student satisfaction in the satisfied category. Overall the level of satisfaction from the 5 dimensions of tangible, reliability, responsiveness, assurance, and empathy has a score of 4.25, meaning that the level of student satisfaction with academic services in the Agribusiness Study Program, Faculty of Agriculture, Bengkulu University is classified as satisfied.